Structural dynamics in the La-module of La-related proteins. Issue 2 (1st February 2021) - Lizarrondo, Javier; Dock-Bregeon, Anne-Catherine; Martino, Luigi; Conte, Maria R
ABSTRACT: The La-related proteins (LaRPs) are a superfamily of eukaryotic RNA-binding proteins with important and varied roles. To understand LaRP functions it is essential to unravel the divergent features responsible for their RNA target selectivity, which underlie their distinct identities and cellular roles. LaRPs are built on a common structural module called the 'La-module' that acts as a main locus for RNA recognition. The La-module is comprised of two tethered domains whose relative structural and dynamic interplay has been proposed to regulate RNA-target selection, albeit the mechanistic underpinning of this recognition remains to be elucidated. A main unsolved conundrum is how conserved La-modules across LaRPs are able to bind to extremely diverse RNA ligands. In this work, we employed Small Angle X-ray Scattering (SAXS) to investigate several human LaRP La-modules in the absence and, where applicable, in the presence of their RNA target, with the aim to explore the structural dynamics of their RNA recognition and provide information on the architectural landscape accessible to these proteins. Integration of these SAXS experiments with prior X-ray crystallography and NMR data suggests that RNA binding is generally accompanied by a compaction and loss of flexibility of the La-module. Nonetheless, the La-modules appear to experience a considerably different degree of inherent flexibility in their apo state. Furthermore, although they all exist in discrete subsets of accessible populations in equilibrium, these vary from LaRP to LaRP and can be either extended or compact. We propose that these divergent features may be critical for RNA substrate discrimination.